2022
DOI: 10.1177/10790632221098341
|View full text |Cite
|
Sign up to set email alerts
|

Pedohebephilia and Perceived Non-coercive Childhood Sexual Experiences: Two Non-matched Case-Control Studies

Abstract: Research on the link between childhood sexual abuse experiences (CSAE) and pedohebephilia is limited by its focus on events that the respondents rate as abusive. We asked 199 German-speaking (Study 1) and 632 English-speaking (Study 2) men with and without self-reported pedohebephilia to complete the Childhood Trauma Questionnaire (CTQ) and scales to assess perceived non-coercive childhood sexual experiences with adults (PNCSE-A), and peers (PNCSE-P, only Study 2). A substantial number of participants with PNC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…It is assumed that individuals who were sexually abused during their childhood become sexually attracted to children during adulthood and may have the desire to sexually offend against children because they repeat the abuse they experienced as children. At least, self-experienced sexual abuse is more common among men with SIC than among others (e.g., [15]). Some participants in the present study reported non-abusive sexual experiences as the reason for their SIC.…”
Section: Results and Discussion Subjective Causes Of Sicmentioning
confidence: 99%
“…It is assumed that individuals who were sexually abused during their childhood become sexually attracted to children during adulthood and may have the desire to sexually offend against children because they repeat the abuse they experienced as children. At least, self-experienced sexual abuse is more common among men with SIC than among others (e.g., [15]). Some participants in the present study reported non-abusive sexual experiences as the reason for their SIC.…”
Section: Results and Discussion Subjective Causes Of Sicmentioning
confidence: 99%